If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-13+28=-5(x+5)
We move all terms to the left:
-13+28-(-5(x+5))=0
We add all the numbers together, and all the variables
-(-5(x+5))+15=0
We calculate terms in parentheses: -(-5(x+5)), so:We get rid of parentheses
-5(x+5)
We multiply parentheses
-5x-25
Back to the equation:
-(-5x-25)
5x+25+15=0
We add all the numbers together, and all the variables
5x+40=0
We move all terms containing x to the left, all other terms to the right
5x=-40
x=-40/5
x=-8
| 8(x+4)-6=26 | | -14(3a+6)=12(6-4a+12) | | 0.5x-0.25=1 | | -14(3a+6)=12(6-4a+12 | | -8+6(3u-10)=u | | 15+30=-5(9x-9) | | z=36z^2+2z+106z2+2z+10 | | -1+c=-9+2c | | X/2-x-4/6=5/3. | | 3m=-3(2m+9) | | 2(3x+5)=-28+26 | | 2(6x+3)=3(3x-9 | | 3(-x-3)=4x+9-7x | | 3(-6+2j)=-2(2j-1) | | 1/2x-10=22 | | 2(3x+8)=-28+2 | | r+8.1=-3.9 | | 3+6d=7+6+8d | | 7+4y=-5,y= | | 8x−5=10x−7 | | 6z-3z-1=2z+7 | | 8x-5=10x-78x−5=10x−7 | | 11/5y-3=-2 | | 11-4x-7-6=6 | | 24=33+x | | 12x-15=3(2x+13) | | x+16+x=21 | | -2(8-3h)=2(-6+4h) | | 20x+16=21 | | -5(2+3x)-4x=28 | | |x+2|=|2x+6|+1 | | -8g-1=-9g+9 |